Cover. (27th February 2019) - Caruso, Tancredi; Schaefer, Ina; Monson, Frank; Keith, Aidan M.
Abstract : Front cover : The cover image of four common oribatid mite species in the families Galumnidae, Nothridae, Oppiidae, and Phthiracaridae, is based on the Research Paper Oribatid mites show how climate and latitudinal gradients in organic matter can drive large-scale biodiversity patterns of soil communities by Tancredi Caruso et al., DOI:10.1111/jbi.13501 .